Progression of hearing loss and choice of hearing aids by patients in their 60s, 70s, and 80s and older: experience in the Japanese super-aged era. (2nd December 2019) - Maeda, Yukihide; Kariya, Shin; Fujimoto, Shohei; Sugaya, Akiko; Kataoka, Yuko; Nakagawa, Atsuko; Tanaka, Satomi; Hosokawa, Natsumi; Nishizaki, Kazunori
Abstract: Background: Demographic data of patients with sensorineural hearing loss (SNHL) in super-aged societies are still limited. Aims/objectives: To report audiometric statistics of SNHL and hearing aid (HA) use in patients in their 60s, 70s, and 80s and older during the super-aged era. Material and methods: Medical charts and audiograms of 2064 older patients with SNHL who visited a Japanese University Hospital in 2007–2018 were retrospectively reviewed. Among 270 patients referred to the HA service unit (HASU), the percentage of final decisions to continue using HAs was calculated. Results: The average pure tone thresholds on initial visit to the clinic were 56.9, 60.6, 69.4, and 82.4 dB HL in patients in their 60s, 70s, 80s, and 90s, respectively. The rates of progression were 0.25, 0.87, 1.19, and 1.37 dB/year in patients in their 50s, 60s, 70s, and 80s, respectively. The percentage of patients in HASU who chose to use HAs did not differ among the 60s (59.3%), 70s (51.2%), and 80s and older (58.2%). Conclusions and significance: The clinical picture of patients with SNHL in their 70s and 80s differs because progression accelerates exponentially through these ages. HAs can be recommended to older adult patients in all the age groups.